Research of the Speed Control Method of Robot - Yin liang (Jixie chuandong)
The velocity curve not smooth and the sudden change of acceleration will appear when the robot start or stop,resulting in body shock,vibration etc. In the process of robot movement,that no sudden change of acceleration,small changes in velocity and smooth transition in every stages of the movement should be ensured so as to reduce the impact and many other problems due to the change of the speed and the acceleration.Focusing on the above cases,the velocity control of the palletizing robot is studied. Now common acceleration and deceleration method include linear acceleration and deceleration method,exponential acceleration and deceleration method,polynomial acceleration and deceleration method,parabola acceleration and deceleration method and S curve acceleration and deceleration method etc. The linear acceleration and deceleration method,exponential acceleration and deceleration method and polynomial acceleration and deceleration method are analyzed emphatically.